Implementation of a Scientific Learning Strategy Approach to Students’ Competence in Writing Short Stories in Class VIII - Ritonga, Islah Hayati; Arfanti, Yulia (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to know: 1) The effect of scientific approach on students' ability to write short stories in class VIII of SMP Swasta Muhammadiyah 25 Rantau Parapat Labuhan Batu Regency learning year 2023-2024; 2) The difference in students' ability to write short stories with learning using the scientific approach with the Contectual Learning Teaching (CTL) approach in class VIII of SMP Swasta Muhammadiyah 25 Rantau Parapat Labuhan Batu Regency learning year 2023-2024. The population in this study were class VIII students of SMP Swasta Muhammadiyah 25 Rantau Parapat Labuhan Batu Regency for the learning year 2023-2024 as many as 7 classes, each class of 36 people. The population of this research is 252 people. The sampling technique used is the classter random sampling technique. The research sample consisted of 2 classes, namely a control class and an experimental class, each of which consisted of 36 children. Data collection techniques with instruments in the form of data tests of students' abilities in writing short stories. This research uses quantitative methods with a pseudo-experimental approach. The data analysis technique used is the t-test with two tailed paired sample t-test (two paired samples) at a significant level of α = 0.05. The results of hypothesis testing showed that: (1) There is an influence of scientific approach on students' ability to write short stories in class VIII of SMP Swasta Muhammadiyah 25 Rantau Parapat. This is known based on the t-test of scientific approach in the pre-test and post-test is (tcount 2.54> ttable 1.99). While in the CTL approach during the pre-test and post-test based on the t-test results found that (tcount 0.05 < ttable 1.99); (2) There is a difference in students' ability to write short stories with learning using a scientific approach with an approach that uses a CTL approach.